2002
DOI: 10.1259/bjr.75.899.750916
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal bone cyst of the ethmoid bone

Abstract: Aneurysmal bone cysts (ABCs) are benign, slow growing expansile lesions usually found in long bones or vertebrae. Plain radiography reveals expansion of bone and cortical thinning. MRI may assist in diagnosis by virtue of its ability to demonstrate blood-fluid levels, which is a characteristic finding in these lesions. Very few cases of ABC of the paranasal sinuses have been reported in the literature. We present MRI findings of ABC of the ethmoid sinus in a 19-year-old male.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…Rarely the lesion may involve multiple bones. Involvement of other bones of the face, such as the zygoma and zygomatic arch, sphenoid, ethmoid, orbit, temporal bone, has also been reported (Carmicheal et al, 1989;Hrishikesh et al, 2002;Cakirer et al, 2002;Tuna et al, 2003;Karim and Haque, 2005). The mandible is the most commonly affected with a higher predilection for the molar areas (Kaffe et al,1999;Motamedi et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Rarely the lesion may involve multiple bones. Involvement of other bones of the face, such as the zygoma and zygomatic arch, sphenoid, ethmoid, orbit, temporal bone, has also been reported (Carmicheal et al, 1989;Hrishikesh et al, 2002;Cakirer et al, 2002;Tuna et al, 2003;Karim and Haque, 2005). The mandible is the most commonly affected with a higher predilection for the molar areas (Kaffe et al,1999;Motamedi et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Depending on its location, other signs/symptoms can be found like headache, diplopia, loss of vision, proptosis, epistaxis, etc. (Hrishikesh et al, 2002;Jordan et al, 1983;Kransdorf and Sweet, 1995;Mendenhall et al, 2006;Ruiz de la Cuesta et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature shows that pain and swelling are the main symptoms and last for as long as 6 months [1, 4, 15]. Other symptoms described include: presence of a palpable mass, different types of neurological problems, usually an ABC located on the spine, and cyst-induced fractures [1, 2, 7, 8, 16]. In our case, there had been a strikingly short period of time between the trauma and the onset of the first symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…ABC is a usually solitary fibro-osseous bone lesion that can occur in any part of the skeletal system, though mainly in the long bones and most frequently in the femur, tibia, humerus, pelvis, fibula. It is very rarely seen in the scull (less than 1% of all ABCs) [1,2,3,4,5]. Reviewing 61 cases, Sheikh [4 ]observed that a greater number of ABCs occurred in the temporal and occipital bones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation